The view of intelligence technology in the learning sector - AlFarsi G.; Yusof A.B.M.; Tawafak R.M.; Malik S.I.; Mathew R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Education computing; Engineering education; A learning system; Artificial intelligence technologies; Educational process; High educations; Human mind; Roberts; Technological breakthroughs; Technology; Learning systems